Primary urethral cancer: Treatment patterns, responses and survival in localized, advanced and metastatic patients - Ilfad Blazevic; Aude Fléchon; Géraldine Pignot; Benoît Mesnard; Jérôme Rigaud; Mathieu Roumiguié; Michel Soulié; Constance Thibault; Laurence Crouzet; Camille Goislard De Monsabert; Felix Lefort; Marine Gross‐Goupil; et al. (BJUI Compass)
Abstract Introduction Primary urethral cancer (PUC) is rare, and limited data exist on optimal treatment and survival, particularly in metastatic cases. The objective of this study was to describe treatment patterns, responses and survival in a contemporary cohort. Patients and Methods Data from patients diagnosed with PUC between January 1, 2000 and December 31, 2018, were retrospectively collected from nine French tertiary centres. To enhance the statistical power of survival analysis in the metastatic stage, patients with synchronous and metachronous metastatic disease were pooled. Results We identified 71 patients (62% males, 38% females). The most common histological types were urothelial (40.0%), squamous cell (34.3%) and adenocarcinomas (14.3%). At diagnosis, 35.2% had localized disease, 49.3% had locally advanced disease and 15.5% had distant metastases. Twenty‐seven patients had a metachronous metastatic cancer. Multimodal therapy was used in 24% of localized and 57.1% of locally advanced disease. Among the 60 patients with non‐metastatic disease, median disease‐free survival (DFS) was 21.2 months. Nodal involvement was associated with worse DFS (HR: 2.03, p = 0.039), while multimodal treatment did not improve DFS (HR: 1.22, p = 0.5419). For metastatic patients, median overall survival was 15.2 months, and progression‐free survival was 6.4 months. Main study limitations were an overrepresentation of locally advanced disease and the small cohort size. Conclusions This retrospective study highlights the significant heterogeneity in terms of histology, stage at diagnosis and treatment of PUC. This study is one of the few to describe treatments and survival in metastatic PUC patients. Efforts must be made to improve survival in these patients.